Интегративный мониторинг интрацеребрально осложненного ишемического инсульта - Дарий, В. И.; Мищенко, Т. С.; Сериков, K. B.; Дарій, Володимир Іванович; Dariy, V. I.; Mishchenko, T.; Serikov, K. (My University, 2019)
The severity of neurological deficit according to the NIHSS scale, for critical patients with an intracerebral complications of ischemic stroke (ICIS), corresponded to severe ischemic stroke in both the group of surviving patients (15,5±0,4 points) and the group of deceased patients from ICIS (16,1±0,6 points). At a time when the predictors of an unfavorable result of 21 critical patients with an ICIS were cerebral perfusion pressure <50 mm Hg. (p<0,05), cardiac index ˂1,8 L×min-1×m-2 (p<0,05), oxygen delivery index ˂280 mL×min-1×m-2 (p<0,05), plasma osmolality > 325 mmol×L-1 (p<0,05), progression of diastolic destabilization > 20% (p<0,05). The severity of systolic destabilization (SD) indicates the presence of systemic vasospasm and determines the need for the correction of hypertension. The achievement of hemodynamic autoregulation is characterized by the limits of normal hemodynamic stabilization (HS) values (0,636-0,599). Diastolic destabilization (DD) indicates a decrease in the pumping function of the heart, which requires immediate inotropic support.
Integrative monitoring for intracerebral complications of ischemic stroke
Keywords: intracerebral complications of ischemic stroke; integrative monitoring; oxygen-transport status; intensive therapy